The Ixodes scapularis Symbiont Rickettsia buchneri Inhibits Growth of Pathogenic Rickettsiaceae in Tick Cells: Implications for Vector Competence - Cull, Benjamin; Burkhardt, Nicole Y.; Wang, Xin-Ru; Thorpe, Cody J.; Oliver, Jonathan D.; Kurtti, Timothy J.; Munderloh, Ulrike G. (Frontiers in Veterinary Science, 2022)
Ixodes scapularis is the primary vector of tick-borne pathogens in North America, but notably does not transmit pathogenic Rickettsia species. This tick harbors the transovarially-transmitted endosymbiont Rickettsia buchneri, which is widespread in I. scapularis populations, suggesting that it confers a selective advantage for tick survival such as providing essential nutrients. The R. buchneri genome includes genes with similarity to those involved in antibiotic synthesis. There are two gene clusters not found in other Rickettsiaceae, raising the possibility that these may be involved in excluding pathogenic bacteria from the tick. This study explored whether the R. buchneri antibiotic genes might exert antibiotic effects on pathogens associated with I. scapularis. Markedly reduced infectivity and replication of the tick-borne pathogens Anaplasma phagocytophilum, R. monacensis and R. parkeri were observed in IRE11 tick cells hosting R. buchneri. Using a fluorescent plate reader assay to follow infection dynamics revealed that presence of R. buchneri in tick cells, even at low infection rates, inhibited the growth of R. parkeri by 86 - 100% relative to R. buchneri-free cells. In contrast, presence of the low-pathogenic species R. amblyommatis or the endosymbiont R. peacockii only partially reduced infection and replication of R. parkeri. Addition of host-cell free R. buchneri, cell lysate of R. buchneri-infected IRE11 or supernatant from R. buchneri-infected IRE11 cultures had no effect on R. parkeri infection and replication in IRE11, nor did these treatments show any antibiotic effect against non-obligate intracellular bacteria E. coli and S. aureus. However, lysate from R. buchneri-infected IRE11 challenged with R. parkeri showed some inhibitory effect on R. parkeri infection of treated IRE11, suggesting that challenge by pathogenic rickettsiae may induce the antibiotic effect of R. buchneri. This research suggests a potential role of the endosymbiont in preventing other rickettsiae from colonizing I. scapularis and/or being transmitted transovarially. Confirmation that the observed inhibition is linked to R. buchneri’s antibiotic clusters requires further investigation but could have important implications for our understanding of rickettsial competition and vector competence of I. scapularis for rickettsiae.